2014
DOI: 10.1016/j.aat.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of morphine-induced dependence and tolerance by ceftriaxone and amitriptyline in mice

Abstract: Results indicate that the treatment with ceftriaxone and amitriptyline, alone or in combination, could attenuate the development of morphine-induced tolerance and dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The analgesic effects of NSAIDs like diclofenac, paracetamol, aspirin, and metamizol, can be abolished by the opioid receptor antagonist, NLX [Vanegas et al, ]. It has also has been reported that CXF, but not CLAV, attenuates the development of tolerance to the antinociceptive effect of morphine and reduces NLX‐precipitated withdrawal [Habibi‐Asl et al, ; Hajhashemi and Dehdashti, ]. In both cases, the effects evaluated may be related to release of endogenous opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effects of NSAIDs like diclofenac, paracetamol, aspirin, and metamizol, can be abolished by the opioid receptor antagonist, NLX [Vanegas et al, ]. It has also has been reported that CXF, but not CLAV, attenuates the development of tolerance to the antinociceptive effect of morphine and reduces NLX‐precipitated withdrawal [Habibi‐Asl et al, ; Hajhashemi and Dehdashti, ]. In both cases, the effects evaluated may be related to release of endogenous opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine suppresses many types of pain, but tolerance, physical dependence, and unwanted side effects limit its clinical use (Trang et al, 2007). Identification of therapeutic strategies for blocking opioid tolerance and dependence has therefore evolved as an area of intense research interest (Habibi-Asl et al, 2014;Mansouri, et al, 2015;Hassanipour et al, 2016;Hosseinzadeh et al, 2016). Adjunctive pharmacotherapies that combine mechanistically distinct analgesics represent one such approach.…”
Section: Introductionmentioning
confidence: 99%
“…This method was performed, according to Habib-Asl [ 26 ]. Mice were divided into four groups ( n = 7 per group) as follows: (1) daily injection of saline, (2) daily injection of morphine (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%